POLITIK EKOWISATA: STRATEGI RENCANA PENGEMBANGAN WISATA PESISIR DI KAWASAN EKONOMI KHUSUS (KEK) PANTAI TIMUR SUNGAILIAT - Risky Ananda Putri (LPPM Universitas Abdurrab, 2022)
Bangka Island is known as a tin-producing area, especially in Bangka Regency. Tin, which is known as black diamond, if exploited continuously, leaves environmental damage and changes in the landscape. Not only tin resources, other potentials are found in the beauty of ecotourism. The Bangka Regency Government supported by PT. Sungailiat East Coast (private sector) compiles a planning strategy for the development of Tourism SEZs on the Sungailiat East Coast which is contained in one of the regional development missions to change the direction of community income from mining to tourism actors. This research method is carried out qualitatively through in-depth interviews and documentation of local regulations. The results of this study indicate that the tourism SEZ planning strategy on the Sungailiat East Coast is in the planning stage. However, such planning can be described as â€œhalf-heartedâ€ planning. This condition is caused by the local government and PT. Sungailiat East Coast did not examine in depth the Mining Business Permits (IUP) located in sea and land waters which are close to the SEZ planning location. In addition, unconventional tin (TI) â€œfloodedâ€ the Sungailiat East Sea. As a result, coastal areas are affected by abrasion due to the actions of tin miners. Then the point of the planning location is next to critical land, and there is no community intervention in the planning activities of the Sungailiat SEZ which is carried out in the ecotourism corridor.